Rancang Bangun Sistem E-Recruitment Karyawan Pada Intrack Market Services Sdn Bhd - Guntur Hertanto; Eva Zuraidah (STMIK Budi Darma, 2022)
The Covid-19 outbreak in our country has forced the acceleration of the digitalization era to avoid crowd in many ways, including the recruitment of new employee in targeted countrys. Besides that, Business expansion must continue, therefore looking for potential employees according to the company's competence is very necessary. The previous recruitment system by sending application files directly or by an e-mail followed with face-to-face interview was very difficult due to limited mobility during this pandemic. An e-recruitment system that can be accessed via the internet is expected to be a solution because applicants only need to send via website anywhere anytime and for companies they can do the screening from anywhere. The author starts with the assessment phase of previous research and then makes several UML such as use case diagrams, activity diagrams, deployment diagrams, component diagrams, class diagrams, and sequence diagrams. The author use the RAD method which emphasizes saving time on processing so that it can be immediately implemented using the PHP programming language assisted with framework Laravel and MySQL for the database. After that, do testing with Black Box Testing and prove that the e-recruitment system is able to run well as a company tool in getting employees by minimizing time and cost and being a place for storing applicant files efficiently as expected.